The role of knowledge management in achieving strategic excellence Field research in some Iraqi private banks - Hammad, Ahmed Jadaan; Al-Kubaisy, Dr. Salah Al-Deen (Journal of Economics and Administrative Sciences, 2020)
The purpose of the research is to study the impact of knowledge management (personalization and coding strategy) in achieving strategic excellence in the environment of Iraqi private banks, and the descriptive and analytical research approach has been adopted, so the researcher adopted positive philosophy according to the deductive approach for the purpose of deriving the first research hypothesis from the theoretical side and the research reached a group of The most important results are that the personalization strategy has made great progress in its ability to influence strategic superiority as a responsive variable, as the civil bank departments were successful in employing the changes that occurred in the personalization strategy when introducing more changes in Strategic excellence, and the practical implications of the research were that knowledge management strategies contribute effectively to achieving strategic excellence, the research is based on its intellectual originality on the propositions off (AL- faouri, et al, 2011)( (Hajric, 2018) on knowledge management and its strategies and confirm The work of organizations in the era of knowledge economy on the knowledge economy they possess, which qualifies them to work in the rapidly changing business environment, which led these organizations to change the traditional thinking frameworks for their work, transforming them to rely on the assets and intellectual and knowledge systems that they possess, contrary to what was Previously based entirely on vision and philosophy Leadership, which gives great importance to this subject and try to enter it as a platform in Iraqi banks. On the one hand, on the other hand, the organization's ability to achieve continuous education, improve talents, and direct achievement ideally, can serve the organization and the customer and thus achieve strategic excellence according to the proposals of both (Alnaweigah, 2013), (Eran, et al, 2015). ), And this research is unique in that it combines two variables and in the environment of Iraqi private banks, so it is a review of the literature written on this topic and also dealt with in the analytical side.